802.11s QoS Routing for Telemedicine Service - Muhammad Haikal Satria; Jasmy bin Yunus; Eko Supriyanto (Institute of Advanced Engineering and Science, 2014)
The merits of 802.11s as the wireless mesh network standard provide a lowcost and high independent scalability telemedicine infrastructure. However,challenges in degradation of performance as hops increase and the absent of Quality of Service (QoS) provision need to be resolved. The reliability and timely manner are the important factor for successful telemedicine service. This research investigates the use of 802.11s for telemedicine services. A new model of 802.11s based telemedicine infrastructure has been developed for this purpose. A non deterministic polynomial path selection is proposed to provide end-to-end QoS provisioning in 802.11s. A multi-metric called QoS Price metric is proposed as measurement of link quality. The QoS Price is derived from multi layers values that reflect telemedicine traffic requirement and the resource availability of the network. The proposed solution has modified the path management of 802.11s and added resource allocation in distributed scheme.DOI:http://dx.doi.org/10.11591/ijece.v4i2.5597